1996
DOI: 10.1111/j.1467-8616.1996.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

You Don't Have to be German to be a “Hidden Champion”

Abstract: The “hidden champions” among Germany's medium‐sized companies are becoming a by‐word for students of management. But do hidden champions exist outside Germany? What management processes distinguish them from other companies? And are there lessons from their success for other companies? This article, extracted from the author's forthcoming book, summarises his answers to these questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 2 publications
3
29
0
2
Order By: Relevance
“…Wirtschaftswunder (Germany's post-war economic success) and the success of the German economy in general (Simon 1996). The Mittelstand was crucial to the development of structurally weak regions such as Bavaria and Hesse in post-war times (Ambrosius 1996).…”
Section: Wältring 2000) Today the Term Mittelstand Is Often Associamentioning
confidence: 99%
“…Wirtschaftswunder (Germany's post-war economic success) and the success of the German economy in general (Simon 1996). The Mittelstand was crucial to the development of structurally weak regions such as Bavaria and Hesse in post-war times (Ambrosius 1996).…”
Section: Wältring 2000) Today the Term Mittelstand Is Often Associamentioning
confidence: 99%
“…Yet, he notes, proportionately more employees in these firms regularly spend more time with their customers than their larger rivals. While the hidden champions are not marketing professionals, 'they are closeness-to-customer professionals' (Simon 1996). Cavanagh and Clifford (1986) on smaller companies stated that they had a "sheer dedication to serving customers better than anyone else".…”
Section: The Perspective Of Place: Evidence Of New Marketing In Smallmentioning
confidence: 99%
“…On the one hand, past research has pointed out that family businesses have a higher entrepreneurial drive which can lead to internationalization (Tsao and Lien, 2013). Studies have also found that family ownership can positively influence firms' degree of internationalization (Simon, 1996;Zahra, 2003) based on the argument that family firms possess unique intangible assets and capabilities that help them in their international ventures. Such intangible assets have been cited in the literature as the family members' commitment and dedication to the firm, also called "familiness", increase opportunity recognition (Aldrich and Cliff 2003) and stewardship, which are related to increased market orientation and entrepreneurship (Mitter et al, 2014).…”
Section: Literature Review Family Firms and Internationalization Processmentioning
confidence: 99%